Risk factors correlated with frontal fibrosing alopecia in Criciuma, Santa Catarina: a case-control study - Lara Xavier Bazotti; Leticia Maoletti Teixeira; Ana Paula Naspolini (Sociedade Brasileira de Dermatologia (SBD), 2022)
Introduction: Fibrosing Frontal Alopecia (FFA) is a form of scarring alopecia, in which patients have an irreversible loss of hair follicles, especially in the frontal and temporoparietal regions. The etiopathogenesis is not fully understood, although hypotheses about genetic, hormonal, and behavioral factors, such as the use of sunscreen and facial moisturizers, have already been described. Methods: A case-control study was conducted using an objective questionnaire with 33 questions. Sixty women were evaluated, 30 diagnosed with FFA, and 30 not affected by the disease. Results: The mean age of the sample was 64 years old. 76.7% of patients with FFA and 23.3% of controls used facial sunscreen and the difference was statistically significant (p<0.001). Also, the use of facial moisturizer was significantly higher in patients with alopecia (63.3%) when compared to controls (33.3%; p=0.038). The frequency of use of regular soap on the face was significantly lower in patients with FFA (46.7%) when compared to the control group (83.3%; p=0.006). Conclusion: Results suggest a possible association between FFA and the use of facial products, such as sunscreen and moisturizer, in this population. All patients were menopausal, reinforcing the hormonal relationship with the disease.